ANALISIS PERKEMBANGAN FUNGSI INTERMEDIASI PERBANKAN SYARIAH DI PROVINSI JAWA TIMUR PERIODE TRIWULAN III 2008 – TRIWULAN III 2009 - Fitriningsih Amalo (Jurnal Ekonomi Pembangunan, 2010)
The research purpose are to find out intermediation function development of Syariah Banking in East Java Province (Three Months Period III 2008 – Three Months Period III 2009) and projecting or finding the intermediation function development trend of Syariah Banking in East Java Province (Three Months Period III 2008 – Three Months Period III 2009). The research kind was descriptive statistic. From the fund data to economic sector in East Java, Syariah Banking have not given special attention in funding the largest four sector in East Java, they were PHR, hotel and restaurant, farm, industry, and transportation-communication. For projection or intermediation function development, in each three months period it was developed, and some of them decreasing, that was funding from economic sector. The sectors were industry, construction, trading, and transportation. But it was only projection since everything could be changed in time according to the economic flow happened